Analysis of Risk Factors for Diarrhea in Children Under Two Years of Age at Koja Regional General Hospital, North Jakarta - Lina Mardianti; Fathiyati; M. Adila Rossa; Al-Bahra (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2025)
The purpose of this study was to analyze the risk factors for diarrhea in children under two years old at the Koja Regional General Hospital, North Jakarta. While the specific objective is to identify the relationship between child factors (age, sex, exclusive breastfeeding, nutritional status, measles immunization, hand and nail hygiene) and the risk of diarrhea, maternal factors (age, education, knowledge, habit of washing hands before feeding children with a risk of diarrhea, socioeconomic factors (family income) with a risk of diarrhea, and dominant risk factors for diarrhea in children under 2 years old. This study was an observational study using a retrospective case control study design. The population of this study was pediatric patients treated with diarrhea. The sampling technique used was purposive sampling. The results showed that the incidence of diarrhea had a significant relationship with nutritional status (p value = 0.037), and the habit of mothers washing hands before feeding children (p value = 0.038).